2010
DOI: 10.1167/iovs.09-3949
|View full text |Cite
|
Sign up to set email alerts
|

Combined Treatment with Bevacizumab and 5-Fluorouracil Attenuates the Postoperative Scarring Response after Experimental Glaucoma Filtration Surgery

Abstract: The results provide compelling evidence that combined bevacizumab and 5-FU offers superior antifibrotic effect over monotherapy in a model of glaucoma filtration surgery, while prolonging bleb survival at the same time. A synergistic effect is suggested to be present.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
41
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(47 citation statements)
references
References 33 publications
5
41
0
1
Order By: Relevance
“…The rabbit has been considered as a useful model for evaluating histopathology or clinical outcome in glaucoma surgery. [20][21][22][23]27,28 In addition, it has been known that there are little difference in protein distribution between human and rabbit aqueous humor. 29 Therefore, we believe that our findings may apply to humans to a certain extent.…”
Section: Discussionmentioning
confidence: 99%
“…The rabbit has been considered as a useful model for evaluating histopathology or clinical outcome in glaucoma surgery. [20][21][22][23]27,28 In addition, it has been known that there are little difference in protein distribution between human and rabbit aqueous humor. 29 Therefore, we believe that our findings may apply to humans to a certain extent.…”
Section: Discussionmentioning
confidence: 99%
“…In bevacizumab treated group (Group B and Group D), the rabbits maintained a low IOP for a longer time and a relative long filtering bleb survival function comparing to the BSS and PECE groups, and post-operative inflammatory infiltration is mild, and no toxic effects were observed on the tissue tested. Furthermore, the following 1-2 weeks afterwards GFS is the critical period of scar tissue generated in the conjunctival tissues and filtering aisle [40][41][42]. We observed that PECE hydrogel was slowly degraded after injecting into the anterior chamber of a rabbit eye model and thoroughly degraded in the third week.…”
Section: Discussionmentioning
confidence: 99%
“…How с включением дополнительной группы кроликов для оценки синергизма беваци-зумаба и 5-фторурацила. Наилучшие результаты были отмечены именно в этой группе [34].…”
Section: применение ингибиторов Vegf после фистулизирующих антиглаукоunclassified